Shuyu Capsules Relieve Premenstrual Syndrome Depression by Reducing 5-HT3AR and 5-HT3BR Expression in the Rat Brain - Fang Li; Jizhen Feng; Dongmei Gao; Jieqiong Wang; Chunhong Song; Sheng Wei; Mingqi Qiao (Neural Plasticity)
The effects of the Shuyu capsule on 5-HT3AR and 5-HT3BR expression in a rat model of premenstrual syndrome (PMS) depression and on 5-HT3AR and 5-HT3BR expression and hippocampal neuron 5-HT3 channel current were investigated, to elucidate its mechanism of action against PMS depression. PMS depression model rats were divided into depression and Shuyu- and fluoxetine-treated groups, which were compared to control rats for frontal lobe and hippocampal 5-HT3AR and 5-HT3BR expression and behavior. The depressed model rats displayed symptoms of depression, which were reduced in treated and normal control rats. Frontal lobe and hippocampal 5-HT3AR and 5-HT3BR levels were significantly higher in the model versus the control group and were significantly lower in the Shuyu group. As compared to control rats, the 5-HT3R channel current in the model group was significantly higher; the 5-HT3R channel current in hippocampal neurons treated with serum from Shuyu group rats was significantly lower than that in those treated with model group serum. Thus, PMS depression may be related to 5-HT3AR and 5-HT3BR expression and increased 5-HT3 channel current. Shuyu capsules rectified abnormal 5-HT3AR and 5-HT3BR expression and 5-HT3 channel current changes in a rat model; this finding may provide insight into treating PMS depression.